Cos³ x . Sin 3x + Sin³x . Cos3x
Now, We know,
Cos 3 θ = 4 Cos³θ - 3 Cos θ.
∴ 4 Cos³θ = Cos 3 θ + 3 Cos θ.
∴ Cos³θ = ( Cos 3 θ + 3 Cos θ)/4
∴ Cos³ x . Sin 3x = (Cos 3 x + 3 Cos x)/4 . Sin 3x
Also,
Sin 3θ = 3 Sin θ - 4 Sin³θ
∴ 4 Sin³θ = 3 Sin θ - Sin 3θ
∴ Sin³θ = (3 Sin θ - Sin 3θ)/4
∴ Sin³x . Cos 3x = (3 Sin x - Sin 3x)/4 . Cos 3x
∴ Cos³ x . Sin 3x + Sin³x . 3 Cos x = (Cos 3 x + 3 Cos x)/4 . Sin 3x + (3 Sin x - Sin 3x)/4 . Cos 3x
= 1/4[(Cos 3 x + 3 Cos x)Sin 3x + ( Sin 3x - Sin 3x) . Cos3x
= 1/4[Sin 3x.Cos 3x + Sin 3x. 3Cos x + 3Sin x.Cos 3 x - Sin 3x Cos 3x].
= 3/4[Sin 3x Cos x + Cos 3x Sinx]
(∵ SinA CosB + CosA SinB = Sin(A+B) )
= 3/4[Sin 4x]